PENDIDIKAN ISLAM TRANSFORMATIF SYEIKH NAWAWI AL-BANTANI: UPAYA MEWUJUDKAN GENERASI RELIGIUS-SAINTIFIK - Toni Pransiska (Jurnal Ilmiah Didaktika, 2018)
This article tries to explore the new paradigms of Islamic education. Islamic education transformative on Syekh Nawawi’s perspektive can be an alternative solution to the problems of the state and education in particular. In fact, Islamic educational transformative is the accumulation of the process of transfer of knowledge, transfer of values, transfer of methodology and transformation. Integration of religion sciences (‘ulumuddin) and natural sciences or humanities sciences is a priority in Islamic education transformative. There is no dichotomy and scientific specialization. Ultimately, through this transformative Islamic education can produce output which has a religious personality and competence of science as well. The expectation is the realization of the scientific-religious generation. Become a religionist-scientific and a saintists-religionist.